SO MUCH OWED BY SO MANY TO SO FEW: HOW THE FINANCIAL ADVISORY AND INTERMEDIARIES ACT 37 OF 2002 ADDRESSES “CONFLICT OF INTEREST” - Daleen Millard (Obiter, 2021)
Winston Churchill delivered his famous speech entitled “The Few” after the Battle of Britain of 1940. This historical conflict saw 2353 young men from Great Britain and 574 from overseas, pilots and other aircrew fly at least one authorized operational sortie with an eligible unit of the Royal Air Force or Fleet Air Arm during the period 10 July to 31 October 1940. Although conflict on the scale of a world war cannot be equated to conflicts of interest between financial-services providers (FSPs), representatives and clients, the potential damage that can be caused by intermediaries and representatives who act in their own interest can be devastating to that particular client. In addition, it also has wider implications for the financial-services industry. It is consequently up to the FinancialServices Board (FSB) to ensure that conflict of interest between intermediaries and representatives and clients are managed in anacceptable way. As a matter of background: The FSB was established by the Financial Services Board Act (97 of 1990) and has as its main objective the supervision of financial institutions in order to achieve maximum consumer protection. As such, the FSB acts as statutory registrar of a variety of financial institutions. Hattingh and Millard explain that the FSB is currently in control of the Collective Investment Schemes Control Act, the Financial Services Board Act, Financial Institutions (Protection of Funds) Act , Financial Supervision of the Road Accident Fund Act, Friendly Societies Act, Inspection of Financial Institutions Act, Long-term Insurance Act, Pension Funds Act, Short-term Insurance Act, Supervision of the Financial Institutions Rationalisation Act, the Securities Services Act, and the Financial Advisory and Intermediaries Act. The FSB drafted the FAIS Act with the aim of creating a regulatory structure which regulates the way in which intermediary and advisory services in respect of financial products are rendered. Conflict of interests is but one of the issues that arise between intermediaries, advisors, financial-services providers and clients and the purpose of this note is to analyse a number of key issues introduced by Board Notice 58 of 19 April 2010. This note sets out to explain what the position was before the introduction of the new rules on the management of conflict of interest. It then proceeds to discuss the new definitions that now form part of the legislation. In addition, it discusses the detailed provisions pertaining to conflict of interest and explains what a conflict-of-interest management policy entails. Finally, the note evaluates the new regulations and asks whether they have thepotential to eliminate unfair dealings by advisors and intermediaries and thereby enhancing the professionalism of those who work in the financial-services industry.